KOMUNITAS HERBA TERESTERIAL PADA DUA TIPE AGROFOREST KAKAO DI DESA MATAUE KECAMATAN KULAWI KABUPATEN SIGI - Kartika Maria Tendean; Ramadhanil Ramadhanil; Samsurizal M. Sulaeman (Biocelebes, 2015)
Study about ‘’Terrestrial Herbs Communities in Two Types of Cacao Agroforest at Mataue Village, Sigi Regency of Central Sulawesi was conducted in the period of April to May 2014. The study was aimed to identify the diversity of herbs over the two types of cacao agroforest. The survey method was used in the study. To observe herb diversity single plot (50 x 50 m in size) and 25 sub plots ( 2 x 2 m in size) was established in each forest type.  The result showed that there were fourty two (42) herbs species in complex agroforest and was nineteen (19) herbs species in simple agroforest. In simple agroforest, the highest (INP) 40,89% refers to Elephantopus mollis Kunth (Asteraceae) and the highest (INP) 34,49%  in complex agroforest was belong to Elatostema sp. (Urticaceae). The similarity species index of both cacao agroforest was 55,07%. Keywords: Terrestrial Herbs, Cacao Agroforest, Mataue village.